Crystal structure of 1-(4-hydroxybenzyl)-4-methoxy-9,10-dihydrophenanthrene-2,7-diol from Arundina graminifolia, C22H20O4 - Liu Mei-Feng; Zhang Xing-Yu; Du Yi-Mei; Chen Yan (Zeitschrift für Kristallographie - New Crystal Structures)
C22H20O4, orthorhombic, P212121 (no. 19), a = 11.355(5) Å, b = 15.084(7) Å, c = 20.078(9) Å, V = 3439(3) Å3, Z = 4, Rgt(F) = 0.0382, wRref(F2) = 0.0994, T = 296(2) K.